What I’ve learned about teaching entrepreneurship : perspectives of five master educators - Hytti, Ulla; Matthews, Charles H.; dt ogilvie; Shelton, Lois M.; Winkel, Doan (Edward Elgar Publishing, 2026)
Five master educators share their reflections on what it is like to teach entrepreneurship and the tips and tricks they have developed over their distinguished careers.
Annals of Entrepreneurship Education and Pedagogy - 2025